(untitled) (Bangladesh Journal of Botany, 2008)
Thirteen species of Phacus hitherto not reported from Bangladesh have been described and illustrated. Freshwater ponds at southern districts of Pirojpur and Barisal revealed these presence of the species. Â Key words: Phytoplankton, New records, Bangladesh, Phacus, Ponds doi:10.3329/bjb.v37i1.1564 Bangladesh J. Bot. 37(1): 55-60, 2008 (June)